Second Life of Post-Mining Infrastructure in Light of the Circular Economy and Sustainable Development—Recent Advances and Perspectives - Katarzyna Pactwa (MDPI AG, 2021)
Current EU policy will force a significant reduction of hard coal mines in the near future due to environmental restrictions. There are also numerous non-coal underground mines that will be excavated in the next few years. Taking the above into consideration, it is worth starting to plan further steps in terms of reclamation of these facilities. Within this manuscript, both recently used and novel approaches to underground space reclamation have been reviewed. Selected methods of reclamation were analyzed in terms of their strengths and weaknesses, and the results were compared with the effect of a commonly used approaches (i.e., filling or flooding of underground space after mine termination). The analysis has been performed in the scope of sustainable development. Taking into account the opinion of many stakeholder groups and underground facilities, reuse was considered as an action aimed at fulfilling sustainable development goals and the circular economy concept. Based on numerous surveys, the challenges and opportunities have been determined as well. Finally, most perspectives concerning underground mine reclamation, including environmental impact, social acceptance, and profitability have been proposed and described.